Third-order nonlinear optical properties of methylammonium lead halide perovskite films. Issue 22 (20th May 2016) - Johnson, Justin C.; Li, Zhen; Ndione, Paul F.; Zhu, Kai
Abstract : We report third-order nonlinear coefficient values and decay time kinetics vs. halide composition (CH3 NH3 PbBr3 and CH3 NH3 PbBr2 I), temperature, and excitation wavelength. Abstract : We report third-order nonlinear coefficient values and decay time kinetics vs. halide composition (CH3 NH3 PbBr3 and CH3 NH3 PbBr2 I), temperature, and excitation wavelength. The maximum values of the third-order nonlinear susceptibility χ (3) (∼1.6 × 10 −6 esu) are similar to or larger than many common third-order materials. The source of the nonlinearity is shown to be primarily excitonic in the tribromide film by virtue of its strong enhancement near the exciton resonance. Nonresonant excitation reduces the nonlinearity significantly, as does increasing the temperature. Substitution of one I for one Br also reduces the nonlinearity by at least one order of magnitude, presumably due to the lack of strong exciton resonance in the substituted form. The thin films are stable, highly homogenous (lacking significant light scattering), and simple and inexpensive to fabricate, making them potentially useful in a variety of optoelectronic applications in which wavelength selectivity is important.